Evidence to support a conspecific nature of allopatric cytological races of Anopheles nitidus (Diptera: Culicidae) in Thailand - Siripan Songsawatkiat (2018)
© The Author 2014. Published by Oxford University Press on behalf of the Entomological Society of America. Metaphase karyotype investigation on two allopatric strains of Anopheles nitidus Harrison, Scanlon, and Reid (Diptera: Culicidae) was conducted in Thailand during 2011-2012. Five karyotypic forms, i.e., Form A (X1, Y1), Form B (X1, Y2), Form C (X2, Y3), Form D (X1, X3, Y4), and Form E (X1, X2, X3, Y5) were obtained from a total of 21 isofemale lines. Forms A, B, and C were confined to Phang Nga Province, southern Thailand, whereas Forms D and E were restricted to Ubon Ratchathani Province, northeastern Thailand. Cross-mating experiments among the five isofemale lines, which were representative of five karyotypic forms of An. nitidus, revealed genetic compatibility by providing viable progenies and synaptic salivary gland polytene chromosomes through F2 generations. The results suggest that the forms are conspecific, and An. nitidus comprises five cytological races. The very low intraspecific sequence variations (average genetic distances = 0.002-0.008) of the nucleotide sequences in ribosomal DNA (internal transcribed spacer 2) and mitochondrial DNA (cytochrome c oxidase subunits I and II) among the five karyotypic forms were very good supportive evidence.